Development of mini scale compressed air energy storage system - Alias , Khamis; Zulasyraf , Mohd Badarudin; Azhar , Ahmad; Azhan, Ab. Rahman; Norazhar , Abu Bakar (2011)
Nowadays, we know about the problem of decreasing the source of natural gas fuel, makes the higher fuel cost for Gas Turbine power plant usage. Because of that, the new technology called the Compressed Air Energy Storage system is created. The main concept of this system is use otT-peak power to pressurize air into an underground reservoir, which is then released during peak daytime hour to power Gas Turbine for power production. This project is to design in small scale system where it can use otT-peak electricity to switch on the air compressor to compressed air. Then the compressed air produced will store in high pressure cylinder tank replace the airtight underground caverns. When the air is released from the high pressure tank, the air expands through a micro-turbine which connected single shaft with generator rotor. Then the micro turbine run and rotate generator rotor that convert mechanical energy to electrical energy. Output voltage then will convert from dc to ac voltage